Magnet, and small device, microactuator, and sensor using the magnet

By introducing the yoke portion of soft magnetic material and the magnet portion of hard magnetic material into the Sm-Co alloy-based magnet, and forming a concave and convex shape at the interface, the problem of insufficient surface flux density in the prior art is solved, and efficient magnetization is achieved Feature enhancement and thermal stability enhancement.

CN115997041BActive Publication Date: 2025-02-25TDK CORP
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202180052143.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-08-27
Filing Date
2021-08-26
Publication Date
2025-02-25
Estimated Expiration
2041-08-26

AI Technical Summary

Technical Problem

The existing Sm-Co alloy-based perpendicular magnetic anisotropic film has room for improvement in surface magnetic flux density.

Method used

The yoke portion of the soft magnetic material and the magnet portion of the hard magnetic material are introduced into the magnet, and the concave and convex shape is formed at its interface to increase the surface magnetic flux density. The specific implementation method includes forming a SmCo5 film on the Sm2Co17 film, and improving the surface magnetic flux density by optimizing the crystal orientation and film thickness of the magnet part.

Benefits of technology

The SmCo-based magnet film and small devices with high surface flux density are suitable for applications such as microactuators and sensors, improving the thermal stability and reliability of magnetic characteristics.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115997041B_ABST
    Figure CN115997041B_ABST
Patent Text Reader

Abstract

A magnet includes: a yoke portion made of a soft magnetic material; and a magnet portion made of a hard magnetic material formed on a main surface of the yoke portion, wherein an interface between the magnet portion and the yoke portion is in a concavo-convex shape.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to a magnet, and a small device, a microactuator, and a sensor using the magnet. Background Art

[0002] In the process of miniaturization of various electronic devices, the development of small devices such as micromotors and microactuators installed in these devices is progressing. The size and performance of these devices greatly affect the magnetic properties of the permanent magnets used in the devices.

[0003] As permanent magnets, films of rare earth metal compounds with high energy products have attracted much attention. Among them, SmCo-based magnet films are in great demand in applications requiring thermal stability of magnetic properties due to their high Curie point, and in applications requiring reliability due to their high weather resistance.

[0004] For example, Patent Document 1 discloses a Sm-Co alloy-based perpendicular magnetic anisotropic film having perpendicular magnetic anisotropy in which the easy magnetization axis is oriented in a direction perpendicular to the film surface, and is characterized in that the film is formed on a substrate composed of Cu or a Cu alloy, and the film is composed of an alloy containing Sm and Co.

[0005] Prior art literature

[0006] Patent Literature

[0007] Patent Document 1: Japanese Patent No. 4614046 Summary of the invention

[0008] [Technical problem to be solved by the invention]

[0009] On the other hand, permanent magnet films used in small devices are required to have a high surface magnetic flux density. However, the Sm—Co alloy-based perpendicular magnetic anisotropic thin film disclosed in Patent Document 1 has room for improvement in terms of surface magnetic flux density.

[0010] The present disclosure is developed in view of the above technical problems, and its purpose is to provide a SmCo-based magnetic film with high surface magnetic flux density. The present disclosure is to provide a magnet with high surface magnetic flux density, and a small device, microactuator, and sensor using the magnet.

[0011] [Technical solution to the problem]

[0012] One aspect of the present invention provides a magnet including: a yoke portion made of a soft magnetic material; and a magnet portion made of a hard magnetic material formed on a main surface of the yoke portion, wherein an interface between the magnet portion and the yoke portion has a concavo-convex shape.

[0013] The magnet of one aspect of the present invention includes a yoke portion and a magnet portion, and the interface is in a concave-convex shape, so that the magnetic flux density of the convex portion can be increased relative to the concave portion. Therefore, the surface magnetic flux density of this magnet is high.

[0014] Here, the concavo-convex shape of the interface may be 1.0 < concavo-convex < 2.0. When the concavo-convex exceeds 1.0, the magnetic flux density of the convex portion can be increased relative to the concave portion. When the concavo-convex is less than 2.0, in the heat treatment process of manufacturing the magnet, the temperature of the heat treatment tends to be lowered and the time can be shortened. Therefore, the decomposition of the magnet portion can be suppressed, and the magnetic flux density can be further improved.

[0015] Alternatively, the yoke may contain Sm 2 Co 17 The magnetic part contains SmCo as a soft magnetic material. 5 As a hard magnetic material, Sm 2 Co 17 Formed in SmCo 5 On the main surface, SmCo 5 The crystal orientation [00L] in SmCo 5 Oriented in the thickness direction. 5 The Curie point is as high as 700°C or above, so the thermal stability of magnetic properties is excellent. 5 The crystal orientation [00L] is oriented in the direction perpendicular to the film surface, resulting in a high surface flux. 5 High and soft magnetic Sm 2 Co 17 They exist as a base, and thus they function as a back yoke. Therefore, the surface magnetic flux density of the magnet in one aspect of the present invention is further improved.

[0016] The thickness of the magnetic body may be 1 to 200 μm. 5 When the thickness is 1 μm or more, the surface magnetic flux density tends to be further improved. When the thickness of the magnetic body is 200 μm or less, the magnet of one aspect of the present invention can be applied to small devices.

[0017] Another aspect of the present invention may also be a small device using the magnet. Another aspect of the present invention may also be a microactuator using the magnet. Another aspect of the present invention may also be a sensor using the magnet.

[0018] Another aspect of the present invention provides a SmCo-based magnetic film, comprising: 2 Co 17 Film and formed on Sm 2 Co 17 SmCo on membrane5 Membrane, SmCo 5 The crystal orientation of the film [00L] is 5 However, L is an arbitrary natural number.

[0019] According to another aspect of the present invention, the SmCo based magnetic film comprises Sm 2 Co 17 Membrane, SmCo 5 The crystal orientation of the film [00L] is 5 Since the film is oriented in the thickness direction, a SmCo-based magnetic film having a high surface magnetic flux density can be provided.

[0020] Here, it can also be that SmCo 5 The thickness of the film is 1 to 20 μm.

[0021] [Effects of the invention]

[0022] According to one aspect of the present invention, there are provided a magnet having a high surface magnetic flux density, and a small device, a microactuator, and a sensor using the magnet.

[0023] According to another aspect of the present invention, a SmCo-based magnetic film having a high surface magnetic flux density is provided. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 This is a schematic cross-sectional view of a magnet according to one embodiment of the present invention.

[0025] Figure 2 This is a schematic diagram of a portion cut out from a SEM photograph of a cross section of a magnet according to one embodiment of the present invention.

[0026] Figure 3 This is a schematic cross-sectional view of a SmCo-based magnetic film according to one embodiment of the present invention.

[0027] Figure 4 This is a schematic cross-sectional view of a SmCo-based magnet according to one embodiment of the present invention.

[0028] Figure 5 This is a schematic diagram of a measurement site for confirming the presence or absence of radial orientation.

[0029] Figure 6 This is a schematic cross-sectional view of a method for producing a SmCo-based magnetic film according to one embodiment of the present invention.

[0030] Figure 7 This is a schematic cross-sectional view of a method for producing a SmCo-based magnetic film according to one embodiment of the present invention.

[0031] Figure 8This is a schematic cross-sectional view of a method for producing a SmCo-based magnet according to one embodiment of the present invention.

[0032] Fig. 9 The SmCo magnetic film obtained in Example 2 is 5 X-ray diffraction profile obtained by irradiating the film with X-rays.

[0033] Fig.10 This is a pole diagram obtained by performing EBSD on the SmCo-based magnet obtained in Example 10. DETAILED DESCRIPTION

[0034] <Magnet>

[0035] A magnet according to one embodiment will be described with reference to the drawings.

[0036] like Figure 1 As shown, the magnet 200 of the present embodiment includes a yoke portion 15 made of a soft magnetic material and a magnet portion 17 formed on a main surface of the yoke portion 15 and made of a hard magnetic material.

[0037] The yoke 15 includes a soft magnetic material. Examples of the soft magnetic material include metal Co, metal Fe, metal Ni, and alloys and compounds containing these metals. Examples of such alloys include Sm 2 Co 17 As such a compound, for example, ferrite can be cited.

[0038] The ratio of the soft magnetic material contained in the yoke 15 may be, for example, 80% by mass or more, 85% by mass or more, 90% by mass or more, or 95% by mass or more.

[0039] The thickness of the yoke 15 is not particularly limited and can be appropriately selected depending on the intended use. For example, it can be set to 0.0010 to 1 mm.

[0040] The magnet part 17 is made of a hard magnetic material. Examples of the hard magnetic material include SmCo 5 、Sm 5 Fe 17 (Using Nd 5 Fe 17 type of crystal structure of Sm and Fe), SmFe 7 (Using TbCu 7 type of crystal structure of Sm and Fe alloy), Sm 2 Fe 17 N 3 (Using Pr 2 Mn 17 C 1.77type of crystal structure of Sm, Fe and N alloy), SmFe 12 (Using ThMn 12 type of crystal structure of Sm and Fe alloy), Nd 2 Fe 14 B (using Nd 2 Fe 14 The atomic ratio of atoms contained in these alloys may deviate from the stoichiometric ratio.

[0041] The ratio of the hard magnetic material contained in the magnet portion 17 may be, for example, 80% by mass or more, 85% by mass or more, 90% by mass or more, or 95% by mass or more.

[0042] From the viewpoint that the surface magnetic flux density of the magnet 200 tends to be further improved, the thickness of the magnet portion 17 is preferably 1 μm or more, more preferably 2 μm or more, and more preferably 5 μm or more. From the viewpoint that the magnet 200 can be applied to small devices, the thickness of the magnet portion 17 is preferably 200 μm or less, more preferably 100 μm or less, and more preferably 20 μm or less. The thickness of the magnet portion 17 can be measured by the following method: embedding the magnet 200 with a resin, grinding the obtained sample, thereby exposing the cross section of the magnet 200 from the resin, and observing the exposed cross section of the magnet 200 using a scanning electron microscope (SEM).

[0043] The interface between magnet part 17 and yoke part 15 is concavoconvex. The shape of the interface can be measured by embedding magnet 200 in resin, grinding the obtained sample to expose the cross section of magnet 200 from the resin, and observing the exposed cross section of magnet 200 using a scanning electron microscope (SEM).

[0044] The convexity and concavity of the interface between the magnet portion 17 and the yoke portion 15 is preferably 1.0 < convexity and concavity < 2.0, more preferably 1.15 < convexity and concavity < 1.6, and further preferably 1.2 < convexity and concavity < 1.5. When the convexity and concavity exceeds 1.0, the magnetic flux density of the convex portion can be increased relative to the concave portion. When the convexity and concavity is lower than 2.0, in the heat treatment process of manufacturing the magnet 200, it tends to be possible to reduce the temperature of the heat treatment and shorten the time. Therefore, the decomposition of the magnet portion 17 can be suppressed, and the magnetic flux density is further improved.

[0045] The roughness of the interface between the magnet portion 17 and the yoke portion 15 can be measured by observing the interface using a scanning electron microscope (SEM). Specifically, the magnet 200 is embedded in a resin, and the obtained sample is ground, thereby exposing the cross section of the magnet 200 from the resin. The cross section is observed using an SEM to obtain a reflected electron image. The acceleration voltage when obtaining the reflected electron image is set to 10 to 15 kV, and the WD (working distance) is set to 10 to 15 mm. A portion (rectangle) for analysis is cut out from the obtained reflected electron image, and the cut image is analyzed, thereby calculating the roughness. Figure 2 Schematic diagram of a portion cut out from a SEM photograph (reflected electron image) of a cross section of the magnet 200. Figure 2 As shown, the reflected electron image is cut out in the following manner: one side of the cut-out image and the side on the opposite side of the side intersect with the interface B1 of the magnet part 17 and the yoke part 15 respectively (b1 and b2), and the interface B1 is accommodated between the remaining two sides. In addition, the reflected electron image is cut out in such a way that the length of the straight line connecting b1 and b2 described later becomes more than 100μm. The cut-out image is subjected to image quality adjustment, binary processing, and edge (contour) extraction processing. Then, the length from one end b1 of the interface B1 to the other end b2 is measured in the cut-out image. In addition, the length of the straight line connecting b1 and b2 is measured. In the length reference, the length displayed on the scale bar is used. The convexity and concavity can be calculated by dividing the length of the interface B1 by the length of the straight line connecting b1 and b2. The measurement magnification is 1000 times. The part observed by SEM is set to two or more parts, instead of analyzing only a part. The convexity and concavity is the average value of the convexity and concavity obtained from the images of two or more parts.

[0046] There is no particular limitation on the use of the magnet 200. Since the magnet 200 has a high surface magnetic flux density, it is suitable for use in small devices, such as micromotors, microactuators, and sensors.

[0047] <SmCo-based magnetic film>

[0048] As an example of the magnet according to the above-mentioned embodiment, a SmCo-based magnetic film according to one embodiment will be described. The SmCo-based magnetic film according to one embodiment will be described with reference to the drawings.

[0049] like Figure 3 As shown, the SmCo-based magnetic film 100 of the present embodiment (hereinafter also referred to as “magnetic film 100”) includes a Mo substrate 10, and a SmCo-based magnetic film 100 formed on the Mo substrate 10. 2 Co 17 Film 20, formed on Sm 2 Co 17 SmCo on film 20 5Film 30. In the magnetic film 100, Sm 2 Co 17 Film 20 is the yoke, SmCo 5 The film 30 is a magnetic part.

[0050] The Mo substrate 10 is a metal Mo plate. The purity of Mo in the Mo substrate may be 99 mass % or more, or 99.998 mass % or more. Another substrate may be provided under the Mo substrate 10 .

[0051] The thickness of the Mo substrate 10 is not particularly limited and can be appropriately selected depending on the intended use. For example, it can be set to 0.0010 to 0.5 mm.

[0052] Sm 2 Co 17 Film 20 contains Sm 2 Co 17 As the main phase. 2 Co 17 Is the use of Th 2 Zn 17 An alloy of Sm and Co with a crystalline structure of the type. 2 Co 17 The ratio of Sm atoms to Co atoms in the stoichiometric ratio may also deviate from the stoichiometric ratio. For example, when various elements are added to improve magnetic properties, Sm 2 Co 17 The ratio of Sm atoms to Co atoms in the system may not always be a stoichiometric ratio. 2 Co 17 If Th 2 Zn 17 If the crystal structure of the type is different, the ratio of Sm atoms to Co atoms may also deviate from the stoichiometric ratio.

[0053] In this specification, "serving as the main phase" means that the mass proportion in the film is the largest. 2 Co 17 The film 20 may also have a 2 Co 17 Different phases, for example, other crystalline phases and grain boundary phases. 2 Co 17 Sm in Film 20 2 Co 17 The ratio may be, for example, 70% by mass or more, 80% by mass or more, 90% by mass or more, or 95% by mass or more.

[0054] For Sm 2 Co 17The thickness of the film 20 is not particularly limited and can be appropriately selected depending on the intended use, and can be, for example, 1 to 100 μm. 2 Co 17 The thickness of the film 20 can be measured by embedding the magnetic film 100 in a resin, polishing the obtained sample to expose the cross section of the magnetic film 100 from the resin, and observing the exposed cross section of the magnetic film 100 with a scanning electron microscope (SEM).

[0055] SmCo 5 Film 30 includes SmCo 5 As the main phase. SmCo 5 CaCu 5 An alloy of Sm and Co with a crystalline structure of the type SmCo 5 The ratio of Sm atoms to Co atoms in the SmCo may also deviate from the stoichiometric ratio. For example, when various elements are added to improve magnetic properties, SmCo 5 The ratio of Sm atoms to Co atoms in SmCo may not always be a stoichiometric ratio. 5 Using CaCu 5 If the crystal structure of the type is different, the ratio of Sm atoms to Co atoms may also deviate from the stoichiometric ratio.

[0056] SmCo 5 The film 30 may also have a SmCo 5 Different phases, for example, other crystalline phases and grain boundary phases. About SmCo 5 SmCo in Film 30 5 The ratio of Sm to SmCo can be, for example, 70 mass % or more, 80 mass % or more, 90 mass % or more, or 95 mass % or more. As a heterophase, for example, the content ratio of Sm is 2.5% to 3.5% of SmCo. 5 Higher Sm-rich phase.

[0057] SmCo 5 The crystal orientation [00L] of the film 30 is in SmCo 5 The film is oriented in the thickness direction (i.e., the direction perpendicular to the film surface A1). L is an arbitrary natural number. When L is an arbitrary number, it refers to the same direction. L is 2, for example.

[0058] SmCo 5 The crystal orientation of the film [00L] is 5 Orientation in the thickness direction of the film means that the orientation degree defined in formula (1) is 50% or more. This orientation degree is based on the vector-corrected Lotgering method and represents the sum of the diffraction peaks based on the crystal orientation [00L] component relative to the sum of the diffraction peaks based on the SmCo 5The ratio of the sum of diffraction peaks of the crystal plane (hkl) of the film. From the viewpoint of further improving the surface magnetic flux density of the magnetic film 100, the orientation degree is preferably 60% or more, more preferably 70% or more, and even more preferably 75% or more.

[0059] (1) I in the formula is for SmCo 5 The intensity of the diffraction peak based on the crystal plane (hkl) when the film 30 is irradiated with X-rays. Each diffraction peak belongs to any crystal plane represented by the Miller index. When 2θ is 30 to 60°, SmCo 5 Examples of the crystal plane of the film include the (002) plane, the (111) plane which is a plane inclined with respect to the (002) plane, and the (110) plane which is a plane perpendicular to the (002) plane.

[0060] In the following formula (1), the numerator of the fraction on the right is, for SmCo observed in the range of 2θ=30 to 60° 5 For each diffraction peak of the film, the product of the intensity I of each peak and the vector correction coefficient β given to the crystal plane of each peak is summed up.

[0061] The vector correction coefficient β is the cosine (cosθ) of the angle θ formed by the (00L) plane as the reference plane and each crystal plane (hkl), and has a different value for each crystal plane (hkl) as described below.

[0062] On the other hand, the denominator of the fraction on the right is SmCo in the range of 2θ = 30 to 60° 5 The sum of the intensities I of the diffraction peaks of the film.

[0063]

[0064] From the viewpoint of further improving the surface magnetic flux density of the magnetic film 100, SmCo 5 The thickness of the film 30 is preferably 1 μm or more, preferably 2 μm or more, and more preferably 5 μm or more. 5 The upper limit of the thickness of the film 30 is not particularly limited, and may be, for example, 200 μm or less, 100 μm or less, or 20 μm or less. 5 The thickness of the film 30 can be measured by embedding the magnetic film 100 in a resin, polishing the obtained sample to expose the cross section of the magnetic film 100 from the resin, and observing the exposed cross section of the magnetic film 100 with a scanning electron microscope (SEM).

[0065] About SmCo 5 The Sm 2 Co 17The film surface A1 on the opposite side of the surface in contact with the film 20 may be partially or entirely covered by Sm 2 O 3 Cover or not be covered.

[0066] For Sm 2 Co 17 Membrane 20 and SmCo 5 The total thickness of the film 30 is not particularly limited and can be appropriately changed depending on the application. For example, it may be 0.002 to 0.2 mm.

[0067] The magnetic film 100 may not include the Mo substrate 10. For example, the Mo substrate may be removed by etching or the like after production.

[0068] The magnetic film 100 may include a Co substrate instead of the Mo substrate 10. The purity of Co in the Co substrate may be the same as the purity of Mo in the Mo substrate. The thickness of the Co substrate may be the same as that of the Mo substrate.

[0069] There is no particular restriction on the planar shape of the magnetic film 100, and it can be appropriately set according to the purpose. The shape of the magnetic film 100 observed from the Z-axis direction can be, for example, a square, a rectangle, and a circle. In the case where the shape of the magnetic film 100 observed from the Z-axis direction is a square, the length of one side thereof can be, for example, 0.1 to 100 mm. In the case where the shape of the magnetic film 100 observed from the Z-axis direction is a rectangle, the length of its long side direction can be, for example, 1 to 100 mm, and the length of its short side direction can be, for example, 0.1 to 50 mm. In the case where the shape of the magnetic film 100 observed from the Z-axis direction is a circle, its diameter can be, for example, 0.1 to 50 mm.

[0070] The surface magnetic flux density of the magnetic film 100 is preferably 5 mT or more, more preferably 7 mT or more, and further preferably 10 mT or more. The surface magnetic flux density of the magnetic film 100 can be measured by bringing a probe of a Hall element into contact with the SmCo of the magnetic film 100. 5 The film surfaces A1 of the films are in contact, thereby drawing the film surface A1 and converting the output voltage into magnetic flux density.

[0071] There is no particular restriction on the use of the magnetic film 100. Since the surface magnetic flux density of the magnetic film 100 is high, it is suitable for use in sensors, micromotors and microactuators. There is no particular restriction on the use of the magnetic film 100. Since the surface magnetic flux density of the magnetic film 100 is high, it is suitable for use in small devices.

[0072] (Effect)

[0073] The magnetic film 100 has a soft magnetic Sm 2 Co17 The saturation magnetization of film 20 is higher than that of SmCo 5 Therefore, Sm 2 Co 17 The film 20 functions as a back yoke for collecting magnetic flux. 5 The crystal orientation [00L] of the film 30 is in SmCo 5 The film 30 is oriented in the thickness direction, that is, as SmCo 5 The crystal orientation of the easy magnetization axis [00L] and SmCo 5 The film thickness direction of the film 30 (the direction perpendicular to the film surface A1 (Z-axis direction)) is aligned, and thus the surface magnetic flux density of the magnetic film 100 becomes high. 5 The Curie point is as high as 700°C or more, so it has excellent thermal stability.

[0074] <Cylindrical SmCo magnet>

[0075] As an example of the magnet according to the above-mentioned embodiment, a cylindrical SmCo-based magnet according to one embodiment will be described with reference to the drawings.

[0076] Figure 4 Schematic diagram of a cross section perpendicular to the axial direction of a cylindrical SmCo magnet 300 (hereinafter also referred to as “magnet 300”) according to the present embodiment. The magnet 300 includes a Co substrate 12, and a Sm 2 Co 17 film 20, and formed on Sm 2 Co 17 SmCo on film 20 5 Film 30. In the magnet 300, the Co substrate 12 and the Sm 2 Co 17 Film 20 is the yoke, SmCo 5 The film 30 is a magnetic part.

[0077] The diameter of the Co substrate 12 is not particularly limited and can be appropriately selected according to the application, and can be, for example, 0.1 to 2.0 mm. The purity of Co in the Co substrate 12 may be the same as the purity of Mo in the Mo substrate of the magnetic film 100 of the above embodiment.

[0078] In this embodiment, Sm 2 Co 17 Membrane 20 and SmCo 5 The film 30 may also be different from the Sm film 100 in the above-mentioned embodiment. 2 Co 17 Membrane 20 and SmCo 5 The same is true for the membrane 30 .

[0079] From the viewpoint of further improving the surface magnetic flux density of the magnet 300, SmCo 5 The crystal orientation [00L] of the film 30 is preferably radially oriented in the magnet 300. The presence or absence of radial orientation can be confirmed by the following method. That is, the magnet 300 is embedded in a resin. A portion of the resin is ground so that a cross section of the cylindrical magnet 300 perpendicular to the axial direction is exposed from the resin. The SmCo 5 In the experiment, the SmCo was determined by EBSD (Electron Back Scatter Diffraction Patterns) method. 5 The crystal orientation of the orientation. As far as the measurement location is concerned, Figure 5 As shown, the SmCo 5 In the figure, there are four parts in total: that is, a part Y1 separated in the Y direction perpendicular to the normal direction at the centroid of the cross section, a part Y2 separated in the -Y direction opposite to the Y direction, a part X1 separated in the X direction perpendicular to the Y direction, and a part X2 separated in the -X direction opposite to the X direction. At Y1, the SmCo 5 The extreme point diagram of the crystal orientation [00L] of Y2 is obtained when the XZ plane is the front and Y2 is viewed in the Y direction. 5 The polar diagram of the crystal orientation [00L] of SmCo is obtained when X1 is viewed from the YZ plane and in the -X direction. 5 The extreme point diagram of the crystal orientation [00L] of SmCo is obtained when the YZ plane is viewed from the front and X direction is observed. 5 The polar diagram of the crystal orientation [00L]. The polar diagram is a diagram showing the crystal orientation by stereoscopic projection. In each polar diagram, if the central dot is marked, it is judged to be: SmCo 5 The crystal orientation [00L] is radially oriented in the cylindrical magnet 300.

[0080] The height of the magnet 300 may be, for example, 5 to 30 mm. The diameter of the magnet 300 may be, for example, 0.5 to 3 mm. The surface magnetic flux density of the magnet 300 may be the same as that of the magnetic film 100. The application of the magnet 300 may be the same as that of the magnetic film 100.

[0081] <Method for producing SmCo-based magnetic film>

[0082] {First embodiment}

[0083] Next, a method for manufacturing a SmCo-based magnetic film according to an embodiment of the present invention will be described in detail. The method for manufacturing a SmCo-based magnetic film according to the present embodiment may also be a method, for example, comprising: immersing a Mo substrate 10 in a first plating bath containing an Sm source and a Co source, and forming a SmCo-based magnetic film on at least one main surface of the Mo substrate 10 by electroplating. 2 Co 17 The obtained laminated film 50 is immersed in a second plating bath containing a Sm source and a Co source, and at least the Sm 2 Co 17 The non-oriented SmCo is formed on the main surface of the film opposite to the main surface in contact with the Mo substrate 10. 5 A process for forming a film (hereinafter also referred to as a "second electroplating process"); and a process for heating the obtained alloy film, wherein the molar ratio of the Co source to the Sm source in the second plating bath is smaller than the molar ratio of the Co source to the Sm source in the first plating bath.

[0084] (First plating step and second plating step)

[0085] Figure 6 FIG. 1 is a schematic cross-sectional view of a method for manufacturing a SmCo-based magnetic film according to an embodiment of the present invention. Figure 6 The Mo substrate 10 shown in (a) has Sm formed on its main surface. 2 Co 17 Film 20, obtained Figure 6 (b) shows a Mo substrate 10 and a Sm 2 Co 17 The laminated film 50 of the film 20. Figure 6 In (b), Sm 2 Co 17 The film is shown only on one main surface of the Mo substrate 10, but the Sm 2 Co 17 The film may be formed on the other main surface of the Mo substrate 10 or on the side surface of the Mo substrate 10 .

[0086] In the second electroplating step, at least Sm 2 Co 17 The non-oriented SmCo is formed on the main surface of the film opposite to the main surface in contact with the Mo substrate 10. 5 Thus, we obtain Figure 6 (c) shows a Mo substrate 10, a Sm 2 Co 17 Film 20 and unoriented SmCo 5 The alloy film 70 of the film 40. Figure 6 (c) Unoriented SmCo 5 The membrane is only shown in Sm2 Co 17 On the main surface of the film opposite to the main surface in contact with the Mo substrate 10, SmCo is not oriented. 5 The film may be formed on the other main surface of the Mo substrate 10 or on the side surface of the Mo substrate 10 .

[0087] In the first electroplating step, the Mo substrate 10 is immersed in a plating bath containing an Sm source and a Co source, the Mo substrate 10 is used as a cathode, and a current is passed between the cathode and the anode, thereby Sm ions and Co ions are reduced and precipitated on the main surface of the Mo substrate 10, and Sm is formed on the main surface of the Mo substrate 10. 2 Co 17 Membrane 20.

[0088] In the second electroplating step, the laminated film 50 is immersed in a plating bath containing a Sm source and a Co source, the laminated film 50 is used as a cathode, and a current is passed between the cathode and the anode, thereby Sm ions and Co ions are generated in the Sm 2 Co 17 The main surface of the film 20 is reduced and precipitated. 2 Co 17 Unoriented SmCo is formed on the main surface of the film 20. 5 Membrane 40.

[0089] The plating bath in the first plating step and the second plating step may be a molten salt of the Sm source, the Co source, and an inorganic salt other than the Sm source.

[0090] As the Sm source, for example, SmCl 3 and SmF 3 As a Co source, for example, CoCl 2 and CoF 2 As for the Sm source and the Co source, one kind may be used alone or two or more kinds may be used in combination.

[0091] Examples of the inorganic salt other than the Sm source and the Co source include KCl, LiCl, and NaCl. These inorganic salts may be used alone or in combination of two or more.

[0092] The molar ratio of the Co source to the Sm source in the first electroplating step may be 1.3 or more, so as to effectively form the Sm 2 Co 17 From the viewpoint of the film 20, it is preferably 1.4 or more. The molar ratio of the Co source to the Sm source in the first electroplating step may be 1.5 or less.

[0093] The molar ratio of the Co source to the Sm source in the second electroplating step may be 1.1 or less, so as to effectively form SmCo 5From the viewpoint of the film 40, it is preferably 1.0 or less. The molar ratio of the Co source to the Sm source in the second electroplating step may be 0.9 or more.

[0094] The ratio of the Sm source to the Sm source, the Co source, and the inorganic salts other than the Sm source and the Co source may be, for example, 0.05 to 2 mol % based on the total number of moles of the Sm source and the Co source and the number of moles of the inorganic salts other than the Sm source and the Co source contained in the plating bath. The ratio of the Co source to the Sm source, the Co source, and the inorganic salts other than the Sm source and the Co source may be, for example, 0.025 to 1 mol % based on the total number of moles of the Sm source and the Co source and the number of moles of the inorganic salts other than the Sm source and the Co source contained in the plating bath.

[0095] The plating bath can be adjusted by, for example, drying the inorganic salt to remove water, then heating to a plating temperature described later to melt the inorganic salt, and then adding the Sm source and the Co source to the molten inorganic salt.

[0096] The material of the anode used in the first electroplating step and the second electroplating step is not particularly limited as long as it is a material that can be used as an anode in electroplating, and for example, graphite, glassy carbon, and Mo can be cited. There is no particular restriction on the shape of the anode, and for example, it can also be a rectangular parallelepiped shape. When the anode is a rectangular parallelepiped shape, the thickness of the anode can also be, for example, 0.1 to 10 mm, the length in the long side direction can also be, for example, 10 to 100 mm, and the length in the short side direction can also be, for example, 1 to 50 mm.

[0097] The plating temperature in the first plating step and the second plating step is not particularly limited as long as it is a temperature at which the inorganic salt melts or above, but it is preferred that the plating temperature be 0.05% or higher in order to effectively form Sm 2 Co 17 Film 20 and unoriented SmCo 5 From the viewpoint of the film 40, the temperature is preferably 400°C or higher, more preferably 500°C or higher, and even more preferably 600°C or higher. Here, the plating temperature refers to the temperature of the plating bath during plating.

[0098] The electrolysis method of the first electroplating step and the second electroplating step may also be a constant current. 2 Co 17 Film 20 and unoriented SmCo 5 From the viewpoint of the film 40 , the current value in the electroplating step is preferably 0.05 A or more, more preferably 0.1 A or more, and even more preferably 0.2 A or more.

[0099] The plating time of the first plating step and the second plating step is as long as the Sm having the required thickness can be formed. 2 Co17 Film 20 and unoriented SmCo 5 The film 40 can be appropriately changed according to the current value. In addition, from the viewpoint of efficiency, it is not necessary to set the time longer than necessary, and for example, it may be 1 minute to 60 minutes.

[0100] Sm 2 Co 17 The film 20 preferably comprises Sm 2 Co 17 As the main phase. 2 Co 17 The film 20 may also have a crystalline phase (heterophase) or a grain boundary different from the main phase. The proportion of the main phase may be, for example, 50 mass % or more, 70 mass % or more, or 90 mass % or more. As the heterophase, for example, the content ratio of Sm may be 50 mass % or more than Sm. 2 Co 17 High Sm-rich phase.

[0101] Unoriented SmCo 5 The film 40 preferably comprises SmCo 5 As the main phase. Unoriented SmCo 5 The film 40 may also have a crystalline phase (heterophase) or a grain boundary different from the main phase. The proportion of the main phase may be, for example, 50 mass % or more, 70 mass % or more, or 90 mass % or more. As the heterophase, for example, the content ratio of Sm is 2.5% of SmCo. 5 High Sm-rich phase.

[0102] The obtained alloy film 70 may be cleaned before the heating step described later. The cleaning method is not particularly limited, and examples thereof include organic solvents such as ethanol and water.

[0103] (Heating process)

[0104] In the heating step, the alloy film 70 is heated to a holding temperature, a magnetic field is applied to the main surface of the alloy film 70 in a vertical direction, the alloy film 70 is heated at the holding temperature, and then a magnetic field is applied to the main surface of the alloy film 70 in a vertical direction while cooling. 5 The crystal orientation [00L] of the film 40 changes from unoriented SmCo 5 The film 40 forms a crystal orientation [00L] in SmCo 5 SmCo oriented in the thickness direction of the film 5 Membrane 30.

[0105] There is no particular limitation on the heating rate in the heating process, and for example, it may be 0.1 to 100°C / second. From the viewpoint of further improving the surface magnetic flux density of the magnetic film 100, the holding temperature is preferably 800°C or higher, more preferably 850°C or higher, and further preferably 900°C or higher. From the viewpoint of further improving the surface magnetic flux density of the magnetic film 100, the cooling rate is preferably 5°C / second or higher, more preferably 10°C / second or higher, and further preferably 20°C / second or higher. There is no particular limitation on the applied magnetic field during the temperature holding process and the cooling process, and for example, it may be 2 to 3T.

[0106] Further inhibition of SmCo 5 From the viewpoint of reducing the surface magnetic flux density of the film 30 , the holding time in the heating step is preferably 60 seconds or less, more preferably 30 seconds or less, and even more preferably 15 seconds or less.

[0107] The atmosphere in the heating step is not particularly limited, but an inert gas atmosphere is preferred from the viewpoint of suppressing oxidation. Examples of the inert gas include Ar and N 2 .

[0108] {Second Embodiment}

[0109] A method for manufacturing a SmCo-based magnetic film according to another embodiment is described in detail. The method for manufacturing a SmCo-based magnetic film according to this embodiment may also be a method, for example, comprising: immersing a Co substrate 12 in a plating bath containing an Sm source, and forming a SmCo film on at least one main surface of the Co substrate 12 by electroplating. 2 a step of electroplating the film 25 ; and a step of heating the obtained laminated film 51 .

[0110] Figure 7 FIG. 1 is a schematic cross-sectional view of a method for manufacturing a SmCo-based magnetic film according to an embodiment of the present invention. Figure 7 The Co substrate 12 shown in (a) has SmCo formed on its main surface. 2 Membrane 25, obtained Figure 7 (b) shows a Co substrate 12 and a SmCo 2 The laminated film 51 of the film 25 .

[0111] SmCo 2 The film 25 preferably comprises SmCo 2 As the main phase. SmCo 2 For MgCu 2 An alloy of Sm and Co with a crystalline structure of the type SmCo 2 The ratio of Sm atoms to Co atoms in the SmCo may also deviate from the stoichiometric ratio. For example, when various elements are added to improve magnetic properties, SmCo2 The ratio of Sm atoms to Co atoms in SmCo may not always be a stoichiometric ratio. 2 If MgCu 2 If the crystal structure of the type is different, the ratio of Sm atoms to Co atoms may also deviate from the stoichiometric ratio.

[0112] SmCo 2 The film 25 may also have a crystalline phase (heterophase) or grain boundaries different from the main phase. The proportion of the main phase may be, for example, 50 mass % or more, 70 mass % or more, or 90 mass % or more. As the heterophase, for example, the content ratio of Sm is 2.5% to 3.5% of SmCo. 2 High Sm-rich phase.

[0113] exist Figure 7 (b) SmCo 2 The film 25 is shown only on one main surface of the Co substrate 12, but the SmCo 2 The film 25 may be formed on the other main surface of the Co substrate 12 or on the side surface of the Co substrate 12 .

[0114] In the electroplating step, the Co substrate 12 is immersed in a plating bath containing a Sm source, the Co substrate 12 is used as a cathode, and a current is passed between the cathode and the anode, thereby Sm ions are reduced and precipitated on the main surface of the Co substrate 12, and SmCo is formed on the main surface of the Co substrate 12. 2 Membrane 25.

[0115] The plating bath in the electroplating step may be a molten salt of a Sm source and an inorganic salt other than the Sm source.

[0116] As the Sm source and the inorganic salt other than the Sm source, the same Sm source and the inorganic salt other than the Sm source as those in the method for producing the SmCo-based magnetic film of the first embodiment can be used.

[0117] The ratio of the Sm source to the Sm source and the inorganic salt other than the Sm source may be, for example, 0.05 to 2 mol % based on the total number of moles of the Sm source and the number of moles of the inorganic salt other than the Sm source contained in the plating bath.

[0118] The plating bath can also be adjusted by, for example, drying the inorganic salt to dehydrate it, then heating it to a plating temperature described later to melt the inorganic salt, and then adding the Sm source to the molten inorganic salt.

[0119] The material and shape of the anode used in the electroplating step may be the same as those in the method for producing the SmCo-based magnetic film of the first embodiment.

[0120] The plating temperature in the electroplating step is not particularly limited as long as it is at a temperature at which the inorganic salt melts or above. 2 From the viewpoint of the film 25, the temperature is preferably 400°C or higher, more preferably 500°C or higher, and even more preferably 600°C or higher. Here, the plating temperature refers to the temperature of the plating bath during plating.

[0121] The electrolysis method in the electroplating step may be a constant current. The current value in the electroplating step may be the same as that in the electroplating step in the method for producing the SmCo-based magnetic film of the first embodiment.

[0122] Regarding the plating time of the electroplating process, as long as the SmCo layer with the required thickness can be formed, 2 The film 25 can be appropriately changed according to the current value. In addition, from the viewpoint of efficiency, it is not necessary to set the time longer than necessary, and for example, it may be 1 minute to 120 minutes.

[0123] The obtained laminated film 51 may be cleaned before the heating step described later. The cleaning method is not particularly limited, and examples thereof include organic solvents such as ethanol and water.

[0124] (Heating process)

[0125] In the heating step, the laminated film 51 is heated to a holding temperature and then cooled. 2 and Co reacts to form a Co substrate 12 and SmCo 2 Film 25 forms Sm 2 Co 17 Film 20 and crystal orientation [00L] in SmCo 5 SmCo oriented in the thickness direction of the film 5 Membrane 30.

[0126] The temperature increase rate, the holding temperature, and the temperature drop rate in the heating step may be the same as those in the heating step in the method for producing the SmCo-based magnetic film of the first embodiment.

[0127] The holding time in the heating step may be 1 hour or longer, or 36 hours or shorter.

[0128] The atmosphere in the heating step may be the same as that in the method for producing the SmCo-based magnetic film of the first embodiment.

[0129] Such a magnetic film can be used in MEMS devices such as lens driving actuators for smartphones.

[0130] <Method for producing cylindrical SmCo-based magnet>

[0131] A method for manufacturing a cylindrical SmCo-based magnet according to an embodiment of the present invention is described in detail. The method for manufacturing a SmCo-based magnet according to the present embodiment may also be a method including, for example, immersing a Co substrate 12 in a bath containing an Sm source, thereby forming SmCo on the Co substrate 12 by reaction diffusion. 2 a reaction diffusion step of the film 25 ; and a step of heating the obtained stacked body 52 .

[0132] Figure 8 FIG. 1 is a schematic cross-sectional view of a method for manufacturing a cylindrical SmCo-based magnet according to an embodiment of the present invention. Figure 8 (a) shows a SmCo substrate 12 formed on the Co substrate 12 2 Membrane 25, obtained Figure 8 (b) shows a Co substrate 12 and SmCo 2 A laminate 52 of films 25 .

[0133] SmCo 2 The film 25 preferably comprises SmCo 2 As the main phase. SmCo 2 MgCu 2 An alloy of Sm and Co with a crystalline structure of the type SmCo 2 The ratio of Sm atoms to Co atoms in the SmCo may also deviate from the stoichiometric ratio. For example, when various elements are added to improve magnetic properties, SmCo 2 The ratio of Sm atoms to Co atoms in SmCo may not always be a stoichiometric ratio. 2 As long as MgCu 2 If the crystal structure of the type is different, the ratio of Sm atoms to Co atoms may also deviate from the stoichiometric ratio.

[0134] SmCo 2 The film 25 may also have a crystalline phase (heterophase) or grain boundaries different from the main phase. The proportion of the main phase may be, for example, 50 mass % or more, 70 mass % or more, or 90 mass % or more. As the heterophase, for example, the content ratio of Sm is 2.5% to 3.5% of SmCo. 2 High Sm-rich phase.

[0135] In the reaction diffusion step, the Co substrate 12 is immersed in a bath containing the Sm source, and reaction diffusion occurs between the Sm source dispersed in the bath and the Co substrate 12 on the main surface of the Co substrate 12, thereby forming SmCo on the Co substrate 12. 2 Membrane 25.

[0136] The bath in the reaction diffusion step may be a molten salt of the Sm source and an inorganic salt other than the Sm source.

[0137] Examples of the Sm source include metal Sm and Sm alloys. The Sm source may be used alone or in combination of two or more.

[0138] Examples of inorganic salts other than the Sm source include KCl, LiCl, and NaCl. These inorganic salts may be used alone or in combination of two or more.

[0139] The ratio of the Sm source to the Sm source and the inorganic salt other than the Sm source may be, for example, 1 to 6 mol % based on the total number of moles of the Sm source and the number of moles of the inorganic salt other than the Sm source contained in the bath.

[0140] The bath can also be adjusted by, for example, drying the inorganic salt to dehydrate it, then heating it to the reaction diffusion temperature described later to melt the inorganic salt, and then adding the Sm source to the molten inorganic salt.

[0141] The reaction diffusion temperature in the reaction diffusion step is not particularly limited as long as it is a temperature at which the inorganic salt melts or above, but it is preferred to effectively form SmCo 2 From the viewpoint of the film 25, it is preferably 400° C. or higher, more preferably 500° C. or higher, and even more preferably 600° C. or higher. Here, the reaction diffusion temperature refers to the temperature of a bath when the reaction diffusion is performed.

[0142] Regarding the reaction diffusion time of the reaction diffusion step, as long as the SmCo layer with the required thickness can be formed, 2 The film 25 can be appropriately changed according to the reaction diffusion temperature and the molar concentration of the Sm source in the bath. In addition, from the viewpoint of efficiency, it is not necessary to set the time longer than necessary, for example, it can be 1 hour to 48 hours.

[0143] The obtained laminated body 52 may be cleaned before the heating step described later. The cleaning method is not particularly limited, and examples thereof include organic solvents such as ethanol and water.

[0144] (Heating process)

[0145] In the heating step, the stacked body 52 is heated to a holding temperature and then cooled. 2 and Co reacts to form a Co substrate 12 and SmCo 2 Film 25 forms Sm 2 Co 17 Film 20 and SmCo with a radial orientation of [00L] 5 Membrane 30.

[0146] There is no particular limitation on the heating rate in the heating process, and for example, it may be 0.1 to 100°C / second. From the viewpoint of further improving the surface magnetic flux density of the magnet 300, the holding temperature is preferably 800°C or higher, more preferably 850°C or higher, and further preferably 900°C or higher. From the viewpoint of further improving the surface magnetic flux density of the magnet 300, the cooling rate is preferably 5°C / second or higher, more preferably 10°C / second or higher, and further preferably 20°C / second or higher.

[0147] The holding time in the heating step may be 6 hours or longer, or 36 hours or shorter.

[0148] The atmosphere in the heating step is not particularly limited, but is preferably an inert gas atmosphere from the viewpoint of suppressing oxidation. Examples of the inert gas include Ar and N 2 .

[0149] Example

[0150] Hereinafter, the present invention will be described in more detail by way of examples, but the present invention is not limited to the following examples.

[0151] <Manufacturing of SmCo-based magnetic films>

[0152] [Example 1]

[0153] (First electroplating step)

[0154] KCl and LiCl were mixed in a molar ratio of KCl:LiCl=41.5:58.5 to obtain a mixture. The obtained mixture was dried to dehydrate. The dehydrated mixture was heated to 650°C in a ceramic container by an external heater to melt the mixture. SmCl was added to the molten mixture. 3 and CoCl 2 As Sm source and Co source. KCl and LiCl, SmCl 3 、CoCl 2 The molar ratio is "KCl and LiCl: SmCl 3 :CoCl 2 =100.0:0.5:0.7", the Sm source and the Co source were added in the manner of "=100.0:0.5:0.7". Next, a Mo substrate with a thickness of 0.5 mm was prepared as a cathode, and a graphite plate with a thickness of 1 mm was prepared as an anode. The Mo substrate was cleaned with acetone in advance. The Mo substrate and the graphite plate were immersed in the molten mixture, and the Mo substrate was subjected to the first electroplating by the electroplating method. The plating was performed under the conditions of constant current electrolysis, a plating temperature of 650°C, a current of 0.5A, and a plating time of 5 minutes. Through the first electroplating step, a Sm 2 Co17 A laminated film of a membrane.

[0155] (Second electroplating step)

[0156] The mixture of KCl and LiCl was melted in the same manner as in the first electroplating step. SmCl was added to the molten mixture. 3 and CoCl 2 As Sm source and Co source. KCl and LiCl, SmCl 3 、CoCl 2 The molar ratio is "KCl and LiCl:SmCl 3 :CoCl 2 =100.0:0.5:0.4", and the Sm source and the Co source were added in the manner of "100.0:0.5:0.4". Next, a graphite plate with a thickness of 1 mm was prepared as an anode. The laminated film obtained in the first electroplating step was set as a cathode. The laminated film and the graphite plate were immersed in the molten mixture, and the laminated film was subjected to a second electroplating by electroplating. Plating was performed under the conditions of constant current electrolysis, a plating temperature of 650°C, a current of 0.5A, and a plating time of 5 minutes. By electroplating, Sm 2 Co 17 The non-oriented SmCo 5 Alloy film of membrane.

[0157] (Heating process)

[0158] The obtained alloy film was heated to 900°C. Next, a 3T magnetic field was applied to the alloy film in the vertical direction while the alloy film was heated at 900°C for 5 seconds. Then, a 3T magnetic field was applied to the alloy film in the vertical direction while the alloy film was cooled, thereby obtaining a SmCo magnetic film. The heating rate was set to 100°C / second, and the cooling rate was set to 20°C / second. The atmosphere of the heating process was set to Ar. It was confirmed by an X-ray diffraction measuring device and an energy dispersive X-ray analyzer that the structure of the obtained SmCo magnetic film is that Sm 2 Co 17 Membrane and SmCo 5 The structure of the membrane.

[0159] [Example 2]

[0160] The plating time in the first electroplating step was set to 3 minutes to form Sm 2 Co 17 The non-oriented SmCo film was formed by setting the plating time in the second electroplating step to 15 minutes. 5The same method as in Example 1 was used to obtain a SmCo-based magnetic film except for the above. The SmCo-based magnetic film was confirmed by an X-ray diffraction measuring device and an energy dispersive X-ray analyzing device that the structure of the obtained SmCo-based magnetic film was a structure in which Sm 2 Co 17 Membrane and SmCo 5 The structure of the membrane.

[0161] [Example 3]

[0162] (Electroplating process)

[0163] KCl and LiCl were mixed in a molar ratio of KCl:LiCl=41.5:58.5 to obtain a mixture. The obtained mixture was dried to dehydrate. The dehydrated mixture was heated to 700°C in a ceramic container by an external heater to melt the mixture. SmCl was added to the molten mixture. 3 As Sm source. KCl, LiCl and SmCl 3 The molar ratio is "KCl and LiCl: SmCl 3 =100.0:0.5" to add the Sm source. Next, a Co substrate with a thickness of 0.5 mm was prepared as a cathode, and a graphite plate with a thickness of 1 mm was prepared as an anode. The Co substrate was cleaned with acetone in advance. The Co substrate and the graphite plate were immersed in the molten mixture, and the Co substrate was electroplated by electroplating. The plating was performed under the conditions of constant current electrolysis, plating temperature of 700°C, current of 0.5A, and plating time of 10 minutes. Through the electroplating process, a SmCo layer was formed on the Co substrate. 2 A laminated film of a membrane.

[0164] (Heating process)

[0165] The obtained laminated film was heated to 900°C. Then, the laminated film was kept at 900°C for 21600 seconds without applying a magnetic field to the laminated film. Then, the laminated film was cooled without applying a magnetic field to the laminated film, thereby obtaining a SmCo-based magnetic film. The heating rate was set to 0.15°C / second, and the cooling rate was set to 20°C / second. The atmosphere of the heating process was set to Ar. It was confirmed by an X-ray diffraction measuring device and an energy dispersive X-ray analysis device that the structure of the obtained SmCo-based magnetic film is that Sm is sequentially formed on a Co substrate. 2 Co 17 Membrane and SmCo 5 The structure of the membrane.

[0166] [Examples 4, 6, 7 and 9]

[0167] In addition to the SmCl3 The same method as in Example 3 was used to obtain a laminated film, except that the addition amount of KCl and LiCl was set to 100 mol parts in total, the temperature for melting KCl and LiCl, the plating temperature, the current, and the plating time were set to the values ​​shown in Table 1. The same method as in Example 3 was used to obtain a SmCo-based magnetic film, except that the heating rate, the holding temperature, the holding time, and the cooling rate in the heating process were set to the values ​​shown in Table 3. The X-ray diffraction measuring device and the energy dispersive X-ray analysis device confirmed that the structure of the obtained SmCo-based magnetic film was that Sm was sequentially formed on a Co substrate. 2 Co 17 Membrane and SmCo 5 The structure of the membrane.

[0168] [Examples 5 and 8]

[0169] The same method as in Example 1 was performed except that the plating time in the first electroplating step was set to the value shown in Table 1, and a Sm film having a surface formed on the Mo substrate was obtained. 2 Co 17 In addition to the SmCl 3 and CoCl 2 The same procedure as in Example 1 was performed except that the addition amount of KCl and LiCl to a total of 100 parts by mole, the temperature at which KCl and LiCl were melted, the plating temperature, the current, and the plating time were set to the values ​​shown in Table 2, and a Sm 2 Co 17 The non-oriented SmCo 5 The same method as in Example 1 was followed except that the holding time in the heating step was set to the value shown in Table 3 to obtain a SmCo-based magnetic film. The structure of the obtained SmCo-based magnetic film was confirmed by an X-ray diffraction measuring device and an energy dispersive X-ray analyzing device: a SmCo-based magnetic film is formed in sequence on a Mo substrate. 2 Co 17 Membrane and SmCo 5 The structure of the membrane.

[0170] [Comparative Example 1]

[0171] (Electroplating process)

[0172] KCl and LiCl were mixed in a molar ratio of KCl:LiCl=41.5:58.5 to obtain a mixture. The obtained mixture was dried to dehydrate. The dehydrated mixture was heated to 650°C in a ceramic container by an external heater to melt the mixture. SmCl was added to the molten mixture. 3 and CoCl 2As Sm source and Co source. KCl and LiCl, SmCl 3 、CoCl 2 The molar ratio is "KCl and LiCl: SmCl 3 :CoCl 2 =100.0:0.5:0.4", and the Sm source and the Co source were added. Next, a Mo substrate with a thickness of 0.5 mm was prepared as a cathode, and a graphite plate with a thickness of 1 mm was prepared as an anode. The Mo substrate was cleaned with acetone in advance. The Mo substrate and the graphite plate were immersed in the molten mixture, and the Mo substrate was electroplated by electroplating. The plating was performed under the conditions of constant current electrolysis, a plating temperature of 650°C, a current of 0.5A, and a plating time of 5 minutes. Through the electroplating process, a non-oriented SmCo 5 A laminated film of a membrane.

[0173] (Heating process)

[0174] The obtained laminated film was heated to 700°C. Then, the laminated film was heated for 5 seconds while maintaining the temperature at 700°C without applying a magnetic field to the laminated film. Then, the laminated film was cooled without applying a magnetic field to the laminated film, thereby obtaining a SmCo-based magnetic film. The heating rate was set to 0.1°C / second, and the cooling rate was set to 0.5°C / second. The atmosphere of the heating process was set to Ar. It was confirmed by an X-ray diffraction measuring device and an energy dispersive X-ray analyzer that the structure of the obtained SmCo-based magnetic film is that an unoriented SmCo is formed on a Mo substrate. 5 The structure of the membrane.

[0175] [Comparative Example 2]

[0176] The same procedure as in Comparative Example 1 was performed except that the plating time in the electroplating step was set to 15 minutes to obtain a SmCo-based magnetic film. The structure of the obtained SmCo-based magnetic film was confirmed by an X-ray diffraction measuring device and an energy dispersive X-ray analyzing device: 5 The structure of the membrane.

[0177] [Comparative Example 3]

[0178] The same procedure as in Example 1 was followed except that the plating time in the first electroplating step was set to the value shown in Table 1 to obtain a laminated film. The obtained laminated film was heated to 700°C. Next, the alloy film was heated at 700°C for 5 seconds without applying a magnetic field to the alloy film. Then, the alloy film was cooled without applying a magnetic field to the alloy film, thereby obtaining a SmCo-based magnetic film. The heating rate was set to 0.1°C / second, and the cooling rate was set to 0.5°C / second. The atmosphere of the heating step was set to Ar. It was confirmed by an X-ray diffraction measuring device and an energy dispersive X-ray analyzer that the structure of the obtained SmCo-based magnetic film is that Sm is formed on a Mo substrate. 2 Co 17 structure.

[0179] [Comparative Example 4]

[0180] The same procedure as in Comparative Example 1 was performed except that the plating time in the electroplating step was set to the value shown in Table 2 to obtain a SmCo-based magnetic film. The structure of the obtained SmCo-based magnetic film was confirmed by an X-ray diffraction measuring device and an energy dispersive X-ray analyzing device: 5 The structure of the membrane.

[0181] [Table 1]

[0182]

[0183] [Table 2]

[0184]

[0185] [Table 3]

[0186]

[0187] <Manufacturing of cylindrical SmCo magnet>

[0188] [Example 10]

[0189] (Reaction Diffusion Process)

[0190] Prepare LiCl and dry it to dehydrate it. Heat the dehydrated LiCl to 700°C in a metal Mo container using an external heater to melt it. Add Sm metal powder as a Sm source to the molten LiCl. Add the Sm source in such a way that the molar ratio of LiCl and Sm is LiCl:Sm=100.0:2.5. Next, immerse a cylindrical Co substrate (diameter: 0.5 mm) in molten LiCl. Clean the Co substrate with acetone in advance. Set the reaction diffusion temperature to 700 degrees and the reaction diffusion time to 9 hours. Through the reaction diffusion process, a SmCo layer is formed on the Co substrate. 2 A laminate of films.

[0191] (Heating process)

[0192] The obtained stack was heated to 1050°C. Then, the stack was heated at 1050°C for 24 hours without applying a magnetic field to the stack. Then, the stack was cooled without applying a magnetic field to the stack, thereby obtaining a cylindrical SmCo magnet. The heating rate was set to 0.15°C / second, and the cooling rate was set to 20°C / second. The atmosphere of the heating process was set to Ar. It was confirmed by an X-ray diffraction measuring device and an energy dispersive X-ray analysis device that the structure of the obtained SmCo magnet is that Sm 2 Co 17 Membrane and SmCo 5 The structure of the membrane.

[0193] [Example 11]

[0194] The same procedure as in Example 10 was performed except that the molar ratio of LiCl to Sm in the reaction diffusion step was set to the value shown in Table 4, thereby obtaining a cylindrical SmCo magnet. It was confirmed by an X-ray diffraction measuring device and an energy dispersive X-ray analyzer that the structure of the obtained SmCo magnet was that Sm 2 Co 17 Membrane and SmCo 5 The structure of the membrane.

[0195] [Examples 12 and 13]

[0196] The same procedure as in Example 10 was followed except that the reaction diffusion time in the reaction diffusion step and the diameter of the Co substrate were set to the values ​​shown in Table 4 to obtain a laminate. The same procedure as in Example 10 was followed except that the holding time in the heating step was set to 25 hours to obtain a cylindrical SmCo magnet. The structure of the obtained SmCo magnet was confirmed by an X-ray diffraction measuring device and an energy dispersive X-ray analyzing device to be a SmCo magnet having a structure in which SmCo is sequentially formed on a Co substrate. 2Co 17 Membrane and SmCo 5 The structure of the membrane.

[0197] [Table 4]

[0198]

[0199] <Evaluation of SmCo-based magnetic films>

[0200] [Examples 1 to 9, Comparative Examples 1 to 4]

[0201] The following evaluations were performed on the SmCo-based magnetic films obtained in the respective Examples.

[0202] (Sm 2 Co 17 Membrane and SmCo 5 Determination of film thickness)

[0203] The obtained SmCo magnetic film was embedded in a resin. A portion of the resin was ground to expose the cross section of the SmCo magnetic film from the resin. The exposed cross section was observed using a scanning electron microscope (manufactured by Hitachi High-Tech Co., Ltd., trade name SU5000) to measure the SmCo magnetic film. 2 Co 17 Membrane and SmCo 5 The film thickness of the film. At this time, the observation magnification was adjusted so that the entire film to be measured was included in the field of view. The results are shown in Table 5.

[0204] (SmCo 5 Determination of the degree of orientation of the crystal orientation)

[0205] The SmCo in the obtained SmCo based magnetic film 5 The film was subjected to X-ray diffraction measurement using an X-ray diffraction measuring apparatus (manufactured by Rigaku Corporation, trade name: RINT-2000). CuKα radiation was used in the measurement at room temperature. Based on the peaks in the range of 2θ=30 to 60° in the obtained X-ray diffraction profile, the SmCo 5 The orientation degree of the crystal orientation

[002] . In addition, in the range of 2θ=30-60°, the peaks originating from the (101) plane, (110) plane, (200) plane, (111) plane, (002) plane, (201) plane and (112) plane are measured. The angle θ formed by the (002) plane and each crystal plane, and the vector correction coefficient β are set to the values ​​shown in Table 6. The calculated orientation degree is shown in Table 5. In addition, the X-ray diffraction profile obtained from the SmCo-based magnet film of Example 2 is Fig. 9 Shown in.

[0206] (Measurement of Surface Magnetic Flux Density of SmCo Magnetic Film)

[0207] The probe of a Hall element (manufactured by Asahi Kasei Electronics Co., Ltd., trade name: HG0712) was brought into contact with the SmCo in the obtained SmCo-based magnetic film. 5 The film surfaces of the films were brought into contact with each other to trace the film surfaces, and the output voltage was converted into magnetic flux density, thereby measuring the surface magnetic flux density of the SmCo-based magnetic film.

[0208] (Measurement of Concavity and Concavity of SmCo-Based Magnetic Film)

[0209] The obtained SmCo-based magnetic film is embedded in a resin. A portion of the resin is ground to expose a cross section of the SmCo-based magnetic film from the resin. The exposed cross section is observed using a scanning electron microscope (manufactured by Hitachi High-Tech Co., Ltd., trade name SU5000) to obtain a reflected electron image. The acceleration voltage for obtaining the reflected electron image is set to 10 to 15 kV, and the WD (working distance) is set to 10 to 15 mm. The portion (rectangle) used for analysis is cut out from the obtained reflected electron image. Figure 2 As shown, the reflected electron image is cut out as follows: that is, a certain side of the cut image and the side on the opposite side of the side and Sm 2 Co 17 Membrane and SmCo 5 The interfaces of the membranes are intersected and the interfaces are contained between the remaining two sides. 2 Co 17 Membrane and SmCo 5 The reflected electron image was cut out so that the length of the straight lines at both ends of the interface of the film was 100 μm or more. The cut-out image was subjected to image quality adjustment, binary processing, and edge (contour) extraction processing. In addition, Sm was measured in the cut-out image. 2 Co 17 Membrane and SmCo 5 In addition, in the cut-out image, the length of the interface of the connecting Sm 2 Co 17 Membrane and SmCo 5 The length of the straight lines at both ends of the membrane interface. The length is based on the length shown on the scale bar. 2 Co 17 Membrane and SmCo 5 The length of the film interface is divided by the SmCo link in the cut-out image 5The length of the straight line at both ends of the interface of the film is used to calculate the concavity. The measurement magnification is set to 1000 times. The part observed by SEM is set to more than two parts, rather than analyzing only a part. The concavity is the average of the concavity obtained from the images of more than two parts. The results are shown in Table 5.

[0210] [Table 5]

[0211]

[0212] [Table 6]

[0213] Crystalline surface θ(°) β=cosθ (101) Face 42.4 0.74 (110) Face 90 0 (200) 90 0 (111) Face 57.7 0.53 (002) plane (reference plane) 0 1.00 (201) Face 61.3 0.48 (112) Face 38.4 0.78

[0214] The SmCo-based magnetic film obtained in each example has Sm 2 Co 17 Membrane, SmCo 5 The orientation degree is 70% or more, whereby the surface magnetic flux density reaches 7.6 mT or more.

[0215] <Evaluation of cylindrical SmCo magnet>

[0216] [Examples 10 to 13]

[0217] The following evaluations were performed on the cylindrical SmCo-based magnets obtained in the respective Examples.

[0218] (Sm 2 Co 17 Membrane and SmCo 5 Determination of film thickness)

[0219] The obtained cylindrical SmCo magnet was embedded in a resin. A portion of the resin was ground to expose a cross section of the cylindrical SmCo magnet perpendicular to the axial direction from the resin. The exposed cross section was observed using a scanning electron microscope (manufactured by Hitachi High-Tech Co., Ltd., trade name SU5000) to measure the Sm 2 Co 17 Membrane and SmCo 5 The film thickness of the film. At this time, the observation magnification was adjusted so that the entire film to be measured was included in the field of view. The results are shown in Table 7.

[0220] (SmCo 5 Determination of the crystal orientation of

[0221] The obtained cylindrical SmCo magnet is embedded in a resin. A portion of the resin is ground so that a cross section of the cylindrical SmCo magnet perpendicular to the axial direction is exposed from the resin. 5In the experiment, the SmCo was determined by EBSD (Electron Back Scatter Diffraction Patterns) method. 5 The EBSD measurement device used is Versa3D (trade name, manufactured by EFI). Figure 5 As shown, the SmCo 5 In the embodiment 10, the measured results of Example 10 are set as 4: that is, the part Y1 separated in the Y direction perpendicular to the normal direction on the centroid of the cross section, the part Y2 separated in the -Y direction opposite to the Y direction, the part X1 separated in the X direction perpendicular to the Y direction, and the part X2 separated in the -X direction opposite to the X direction. Fig.10 (a) to (d) show. Fig.10 (a) is the SmCo when the XZ plane is set as the front and Y1 is viewed in the -Y direction 5 Pole diagram of the crystal orientation [00L]. Fig.10 (b) is the SmCo when the XZ plane is set as the front and Y2 is viewed in the Y direction. 5 Pole diagram of the crystal orientation [00L]. Fig.10 (c) is the SmCo when X1 is viewed in the -X direction with the YZ plane as the front. 5 Pole diagram of the crystal orientation [00L]. Fig.10 (d) is the SmCo when the YZ plane is set as the front and X2 is viewed in the X direction. 5 The polar diagram of the crystal orientation [00L]. The polar diagram is a diagram showing the crystal orientation through stereographic projection. Fig.10 In each pole diagram, the center is the crystal orientation [00L]. That is, when the crystal orientation [00L] is facing the front, a dot is placed in the center of the pole diagram. Fig.10 As can be seen from (a) to (d), since the point is placed in the center of the pole diagram, it is confirmed that: SmCo 5 The crystal orientation [00L] of the cylindrical SmCo magnet is radially oriented. The same measurement results as those of Example 10 were obtained in Examples 11 to 13, and thus it was confirmed that: SmCo 5 The crystal orientation [00L] is radially oriented in the cylindrical SmCo magnet.

[0222] (Measurement of Surface Magnetic Flux Density of SmCo Magnets)

[0223] The surface magnetic flux density of the cylindrical SmCo-based magnet was measured in the same manner as the surface magnetic flux density of the SmCo-based magnet film.

[0224] (Measurement of Concavity and Concavity of SmCo-Based Magnetic Film)

[0225] The obtained cylindrical SmCo magnet is embedded in resin. By grinding a part of the resin, a cross section of the SmCo magnet perpendicular to the axis is exposed from the resin. The exposed cross section is observed by a scanning electron microscope (manufactured by Hitachi High-Tech Co., Ltd., trade name SU5000) to obtain a reflected electron image. The acceleration voltage when obtaining the reflected electron image is set to 10-15 kV, and the WD (working distance) is set to 10-15 mm. The part (rectangle) used for analysis is cut out from the obtained reflected electron image. As shown in FIG. Figure 2 As shown, the reflected electron image is cut out in the following manner: a certain side of the cut image and the side on the opposite side of the side and Sm 2 Co 17 Membrane and SmCo 5 The interfaces of the membranes are intersected, and the interfaces are accommodated between the remaining two sides. 2 Co 17 Membrane and SmCo 5 The reflected electron image was cut out so that the length of the straight lines at both ends of the interface of the film was 100 μm or more. The cut-out image was subjected to image quality adjustment, binary processing, and edge (contour) extraction processing. In addition, the connection Sm 2 Co 17 Membrane and SmCo 5 The length of the straight lines at both ends of the interface of the film. In addition, in the cut-out image, the connecting Sm 2 Co 17 Membrane and SmCo 5 The length of the straight lines at both ends of the membrane interface. The length is based on the length shown on the scale bar. 2 Co 17 Membrane and SmCo 5 The length of the membrane interface is divided by the link Sm in the cut-out image 2 Co 17 Membrane and SmCo 5 The length of the straight line at both ends of the interface of the film is used to calculate the concavity. The measurement magnification is set to 1000 times. The part observed by SEM is set to more than two parts, rather than only analyzing a part. The concavity is the average of the concavity obtained from the images of more than two parts. The results are shown in Table 7.

[0226] [Table 7]

[0227]

[0228] [Explanation of symbols]

[0229] 10...Mo substrate, 12...Co substrate (Co base material), 15...Yoke, 17...Magnet, 20...Sm 2 Co 17 Membrane, 25…SmCo 2 Membrane, 30…SmCo 5 Film, 40…Unoriented SmCo 5 Film, 50, 51...Laminated film, 52...Laminate, 70...Alloy film, 100...SmCo-based magnetic film, 200...Magnet, 300...SmCo-based magnet.

Claims

1. A magnet, wherein: have: a yoke comprising a soft magnetic material; and a magnet portion including a hard magnetic material formed on a main surface of the yoke portion, The interface between the magnet part and the yoke part is concave-convex. The concavo-convex shape of the interface has a concavo-convexity of 1.21 or more and 1.94 or less, The yoke contains Sm2Co 17 As a soft magnetic material, The magnet part contains SmCo5 as a hard magnetic material, The Sm2Co 17 formed on the main surface of the SmCo5, The crystal orientation [00L] of the SmCo5 is oriented in the thickness direction of the SmCo5.

2. The magnet according to claim 1, wherein The thickness of the magnetic part is 1 to 200 μm.

3. A small device, wherein: The magnet according to claim 1 or 2 is used.

4. A microactuator, wherein: The magnet according to claim 1 or 2 is used.

5. A sensor, wherein: The magnet according to claim 1 or 2 is used.

6. A method for manufacturing a SmCo magnet, wherein: The SmCo magnet comprises a Co substrate, a Sm2Co 17 Film, and the Sm2Co 17 SmCo5 film on membrane, The manufacturing method comprises: A reaction diffusion step of immersing the Co substrate in a bath containing an Sm source and reacting and diffusing the substrate to obtain a stack having a Co substrate and a SmCo2 film formed on the Co substrate; and The heating step heats the stacked body, thereby causing the Co substrate and the SmCo2 film to react to form the Sm2Co 17 Film and the SmCo5 film.

Citation Information

Patent Citations

  • Anisotropic nanocomposite rare earth permanent magnets and method of making

    CN1985338A

  • Iron base magnetic alloy and magnetic device using the same

    JP1997078208A